Analysis of Purchase Intention Towards MS Glow Skincare Products: (A Study on the Local Community in Cilacap City) - Mei Susilawati; Setyo Pantawis (Cahaya Abadi Publisher, 2026)
The rapid expansion of Indonesia's cosmetic industry has intensified market competition, where MS Glow has emerged as a dominant player despite facing challenges related to negative digital sentiment regarding product quality. This phenomenon is particularly relevant in the context of Cilacap City, characterized by consumers who are price-sensitive yet highly responsive to digital trends. Consequently, this study aims to comprehensively analyze the influence of price perception, social media exposure, and celebrity endorser appeal on consumer purchase intention for MS Glow skincare products in this specific region. Employing a quantitative explanatory approach, primary data were gathered through questionnaires distributed to 97 respondents, selected via purposive sampling criteria based on product awareness and domicile in Cilacap. The data were analyzed using multiple linear regression assisted by SPSS version 25 to test the hypotheses. Empirical findings reveal that price exerts a negative and significant effect on purchase intention, indicating that price increases substantially diminish buying interest. Conversely, social media and celebrity endorsers demonstrate positive and significant effects, with social media emerging as the dominant factor. Collectively, these independent variables contribute an Adjusted R Square of 73.2% to purchase intention. The study's managerial implications suggest that MS Glow should formulate more affordable pricing strategies tailored to regional markets, while simultaneously optimizing creative social media content and selecting relevant public figures to reinforce brand image and drive consumer purchasing decisions.